2003
DOI: 10.5194/acp-3-2083-2003
|View full text |Cite
|
Sign up to set email alerts
|

Operational mapping of atmospheric nitrogen deposition to the Baltic Sea

Abstract: Abstract.A new model system for mapping and forecasting nitrogen deposition to the Baltic Sea has been developed. The system is based on the Lagrangian variable scale transport-chemistry model ACDEP (Atmospheric Chemistry and Deposition model), and aims at delivering deposition estimates to be used as input to marine ecosystem models. The system is tested by comparison of model results to measurements from monitoring stations around the Baltic Sea. The comparison shows that observed annual mean ambient air con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…This decrease is mainly due to the drastic drop in sulphate content in wet deposits and that is in accordance to the research results obtained in different countries (Anderson, Downing 2006;Hertel et al 2003;Schöpp et al 2003;Kopácek et al 1997;EMEP 2004;Matzner 1989) as well as in other places of Lithuania (Jasinevičienė, Šopauskienė 1999;Šopauskienė, Būdvytytė 1994Šopauskienė, Būdvytytė , 1996. For example, sulphate contents in wet deposits decrease almost twice from 1994 to 1998 in the monitoring stations of NPs Aukštaitija, Žemaitija and Dzūkija, the later changes up to 2003 are not significant (Augustaitis et al 2006).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This decrease is mainly due to the drastic drop in sulphate content in wet deposits and that is in accordance to the research results obtained in different countries (Anderson, Downing 2006;Hertel et al 2003;Schöpp et al 2003;Kopácek et al 1997;EMEP 2004;Matzner 1989) as well as in other places of Lithuania (Jasinevičienė, Šopauskienė 1999;Šopauskienė, Būdvytytė 1994Šopauskienė, Būdvytytė , 1996. For example, sulphate contents in wet deposits decrease almost twice from 1994 to 1998 in the monitoring stations of NPs Aukštaitija, Žemaitija and Dzūkija, the later changes up to 2003 are not significant (Augustaitis et al 2006).…”
Section: Discussionsupporting
confidence: 77%
“…Rosenberg et al (1990) estimated that about 50% of the nitrogen load on the overall Baltic Sea arises from atmospheric deposition. Lindfors et al (1993) have found during their field studies that dry deposition contributes to between 10 and 30% of the atmospheric nitrogen input to the Baltic Sea (Hertel et al 2003). The history and forecast of the main emissions in Europe has been compiled and calculated by Schöpp et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Combustion of fossil fuels and intensified agricultural practices now emit huge quantities of nitrogen to the atmosphere, making atmospheric deposition a major nitrogen source for coastal and open marine systems (Duce et al, 2008;Galloway et al, 2004;Paerl, 1995Paerl, , 1997. Recent estimates for the Baltic Sea have atmospheric deposition contributing a quarter to a third of the total estimated external annual load of ∼1 million tons of nitrogen (Hertel et al, 2003;HELCOM 2004). Reduction of airborne emissions is therefore a top priority for most nations but detection of the origin of polluting substances is complex.…”
Section: Atmospheric Nitrogen Deposition In the Baltic Seamentioning
confidence: 99%
“…Using a long-range transport and deposition model he estimated wet and dry deposition of total nitrogen to be 800-1000 mgN m −2 yr −1 in the Baltic Proper area, which is higher than the estimates found in this study (∼600 mg N m −2 yr −1 ). In a recent publication the average load was estimated to 684 kg N km −2 (Hertel et al, 2003) and the Helsinki Commission estimates it to ∼260 ktons N for the year 2000 in the entire Baltic Sea area (420 000 km 2 ) (HEL-COM, 2004). Applying the calculated average annual load of total N-deposition in this study (617 kg N km −2 ) to the same area gives an estimate of ∼259 ktons.…”
Section: Nutrient Loadsmentioning
confidence: 99%
“…Thus areas more than a few hundred km from sources receive most of their N r deposition in precipitation (Bartnicki et al, 2011;de Leeuw et al, 2003;Hertel et al, 2003), except possibly for forests whose aerodynamic roughness maximises dry deposition. Simpson et al (2006) presented calculations of the wet and dry fraction of both oxidised and reduced nitrogen over Europe, calculated with the EMEP MSC-W model for the year 2000.…”
Section: Distribution Between Dry and Wet Depositionmentioning
confidence: 99%